Penampilan Padi Aromatik Varietas Gilirang di Sulawesi Selatan - Ali Imran (Buletin Plasma Nutfah, 2003)
AbstractStudy on the performance of aromatic rice Gilirang variety was conducted at seven districts in South Sulawesi. Five thousand square meters of rice planted based on farmers cultural practices. The rice plant were transplanted at the planting distance of 25 x 25 cm with one plant per hill. In general plants were growing well. The yields were ranging from 4.8-8.1 t/ha with the average of 6.5 t/ha milling rice, which was higher than the check variety Ciliwung, 5.9 t/ha.AbstrakPenelitian dilakukan di lahan sawah irigasi di tujuh Kabupaten di Sulawesi Selatan pada bulan Mei - Oktober 2002. Penelitian menempati area seluas 5 are di tiap lokasi. Padi aromatik varietas Gilirang ditanam dengan jarak 25 x 25 cm, satu batang per rumpun. Hasil penelitian menunjukkan bahwa tanaman tumbuh baik dengan hasil berkisar antara 4,8-8,1 t/ha, rata-rata 6,5 t/ha GKG atau 9% lebih tinggi dari varietas nonaromatik Ciliwung.